Back Cover: The Integrin Ligand c(RGDf(NMe)Nal) Reduces Neointimal Hyperplasia in a Polymer‐Free Drug‐Eluting Stent System (ChemMedChem 7/2014). Issue 7 (July 2014) - Rechenmacher, Florian; Steigerwald, Kristin; Laufer, Burkhardt; Neubauer, Stefanie; Kapp, Tobias G.; Li, Liang; Mas‐Moruno, Carlos; Joner, Michael; Kessler, Horst
<x xml:space="preserve">Abstract</x> The back cover picture shows the release of the peptidic integrin ligand c(RGDf(NMe)Nal) from a polymer‐free drug‐eluting stent to inhibit smooth muscle cell proliferation and as a consequence to reduce neointimal hyperplasia. For more details, see the Full Paper by Horst Kessler et al. on p. 1413 ff.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>